REKONSEPTUALISASI MUSYAWARAH DALAM AL-QUR’AN DAN HADIS BERDASARKAN PENAFSIRAN DAN PEMAHAMAN PRAKTISDI INDONESIA - Misbahuddin Asaad; Basri; Ahmad Ishak (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
This study examines the reconceptualization of deliberation in the perspective of the Qur'an and hadith by tracing textual interpretation and its practical application in the socio-religious context in Indonesia. Deliberation, as a key principle in collective decision-making in Islam, is not only mentioned in verses such as QS. Ash-Shura [42]: 38, but also exemplified by the Prophet Muhammad SAW in various strategic events. However, its meaning and implementation experience dynamics in accordance with the socio-cultural context of Muslim society. This study uses an evidential method and a qualitative-descriptive approach by analyzing classical and contemporary interpretations, as well as case studies of the implementation of deliberation in Islamic institutions and local communities in Indonesia. The results show that deliberation in Indonesia has expanded into an instrument of democratization and public participation, without abandoning the basic values of shura. This reconceptualization shows the integration between Islamic normative values and inclusive local socio-political practices. These findings confirm the importance of deliberation as a means of dialogue, consensus, and strengthening social cohesion in the life of the nation and religion.